Industri Perikanan Jepang Ditinjau dari Perspektif Tata Kelola Global - Kintan Fitria Nur Andini; Andrea Khairina; Hilda Zahara Firdausi; Lucky Azhar Adikusuma (TRANSBORDERS: International Relations Journal, 2022)
Abstract Japan is one of the largest consumers of fishery products in the world. Fisheries play a significant role as a key regional economy, especially for coastal areas. In addition, Japan is also one of the largest exporting countries in the world. In meeting market needs and high consumption, a large supply of fish is needed. However, the methods used by the Japanese seem sadistic and inhumane. Dolphin and whale hunting is considered to be so intense in Japan that it produces a 'domino effect'. Where the hunters started their slaughter from the largest dolphin population to the smaller dolphin population. Japan's actions, which still carry out commercial whaling and dolphin hunting, have drawn criticism from anti-whaling countries. There are many regulations governing this phenomenon, the International Convention for the Regulation of Whaling (ICRW) is one of the regulations issued to reduce overexploitation of whale and small cetacean fishing. However, of the many regulations that exist, there is not a single regulation that is heeded by Japan. In full, this study uses a global governance approach as a reference in interpreting a phenomenon being discussed. So this approach was chosen as the focal point in examining the concept of the role of international political institutions and organizations. Where the apparatus and government have a role in hiding the phenomenon of illegal fishing, especially what happened in Taiji, Japan. Keywords: Illegal Fishing; Fishing Net; Fishing Industry; Climate Change; Environmental Indicators; Global Governance